Strategies to Minimize Adhesions to Intraperitoneally Placed Mesh in Laparoscopic Ventral Hernia Repair - Tran, Hanh (Society of Laparoendoscopic Surgeons, 2012)
INTRODUCTION: Adhesions to mesh/tacks in laparoscopic ventral hernia repair are often cited as reasons not to adopt its evidence-based superiority over conventional open methods. This pilot study assessed the occurrence of adhesions to full-sized Polypropylene and Gore-tex DualMesh Plus meshes and the possibility for adhesion prevention using fibrin sealant. METHODS: Two 10-cm to 15-cm pieces of mesh were placed and fixed laparoscopically in pigs (25kg to 55kg). Group I: 2 animals with Polypropylene mesh on one side and DualMesh on other side. Group II: 2 animals with DualMesh on each side with fibrin sealant applied to the periphery of mesh and staples to one side. Group III: 1 animal with 2 pieces of Polypropylene mesh with fibrin sealant applied to the entire mesh. All animals underwent laparoscopy 3 months later to assess the extent of adhesions, and full-thickness specimens were removed for histological evaluation. RESULTS: More Polypropylene mesh was involved in adhesions than DualMesh. However, with the DualMesh involved in adhesions, more of the surface area was involved in forming adhesions than with Polypropylene mesh. None of the implanted DualMesh had visceral adhesions, while 2 out of 3 Polypropylene meshes had adhesions to both the liver and spleen but none to the bowel. Implanted Polypropylene mesh with fibrin sealant had no adhesions. DualMesh had shrunk more significantly than Polypropylene mesh. Histological evaluation showed absence of acute inflammatory response, significantly more chronic inflammatory response to DualMesh compared to Polypropylene and complete mesothelialization with both meshes. There was extensive collagen deposition between Polypropylene mesh fibers, while fibrosis occurred on both sides of DualMesh with synovial metaplasia over its peritoneal surface akin to encapsulation. CONCLUSIONS: DualMesh caused fewer omental and visceral adhesions than Polypropylene mesh did. Fibrin sealant eliminated adhesions to DualMesh and prevented adhesions to Polypropylene mesh when applied over the entire surface. These results support our current use of DualMesh and fibrin sealant in LVHR.